Belarus Public Expenditure Review : Strengthening the Equity, Efficiency and Effectiveness of Social Expenditures in Belarus - World Bank (World Bank, Washington, DC, 2020)
After more than a decade of strong growth, interrupted only by the 2008-2009 global financial crisis, Belarus’ economy has encountered major headwinds. Since 2012, growth has stalled, macroeconomic imbalances have intensified, and public finances have deteriorated. Unlike regional peers, the country was unable to take advantage of buoyant global demand, ample liquidity and strong risk appetite. This suggests that the causes for this disappointing outcome are domestic and rooted in the current economic model based on an outsized public sector and reliance on Russia for cheap energy and as main export market. The narrow export base has left the economy vulnerable to economic weakness in Russia and, indirectly, to volatility in global oil prices. These shocks have exposed major structural weaknesses, that have dragged down productivity and potential growth and increased Belarus’ vulnerability to major shocks such as the Coronavirus (COVID-19) pandemic. The policy response to the external headwinds has been pro-cyclical. It has focused on avoiding major financial disruptions and resorting to increased foreign borrowing to make it through the financing pressures rather than deeper structural adjustment needed to adjust to the new realities and anchor fiscal sustainability. It has focused on exchange rate adjustment accompanied by ad-hoc fiscal retrenchment. The latter, however, although significant, has been episodic and less than optimal as it has protected consumption at the expense of investment. The scope for fiscal adjustment has been constrained by the structural rigidities of Belarus’ public finances. Looking forward, Belarus now faces a perfect storm of a global economic shock caused by the Coronavirus (COVID-19) pandemic, an unprecedented drop in oil prices, and the phasing out of the energy import price discount by 2024 due to the Russian tax maneuver. All these adverse external developments come against the background of deeply rooted structural rigidities, a heavy debt redemptions schedule and a much-reduced policy space compared with previous episodes of external pressures such as in 2009 and 2015.